Implementing digital literacy-based learning through “Topeng Malangan” using Padlet in an elementary school - Dewi, Radeni Sukma Indra; Kusumaningrum, Shirly Rizki; Mardhatillah, Mardhatillah; Pristiani, Riska; Islami, Kaisra Alfikri; Fitriyah, Siti Ni’matul; Mufidah, Siti (Universitas Jambi, Indonesia, 2026)
This study examines the implementation of digital literacy-based learning through Padlet to support fourth-grade students’ understanding of Topeng Malangan characters at UM Laboratory Elementary School. A qualitative descriptive approach was employed, involving 52 students, with data collected through observation, interviews, questionnaires, and documentation to capture students’ perceptions. The findings show that Padlet promotes interactive, collaborative, and engaging learning environments. Students demonstrated high participation, creativity, and motivation, as reflected in active posting, peer feedback, and multimodal expression. The platform also enhanced students’ understanding of cultural values embedded in Topeng Malangan characters. However, challenges such as limited internet access and varying digital skills were identifiedwhich hindered some students' ability to fully engage with the platform and benefit from its educational resources. Overall, the integration of Padlet supports both digital literacy development and cultural learning, highlighting its potential as an innovative tool for culturally responsive education in elementary schools.